2002
DOI: 10.1046/j.1439-0310.2002.00819.x
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive Signals of Female Lizards: Pattern of Trait Expression and Male Response

Abstract: Relative to the volume of studies concerning the function and evolution of male‐biased sexually dimorphic traits, instances of female‐biased sexual dimorphisms remain largely unstudied, especially in species with conventional sex roles. I investigated the signal function of a female‐specific ornamental trait using the striped plateau lizard (Sceloporus virgatus, Phrynosomatidae) as a model system. During the reproductive season, female S. virgatus develop orange color on their throats that is absent in conspec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
62
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(62 citation statements)
references
References 46 publications
(63 reference statements)
0
62
0
Order By: Relevance
“…Though sample size of non-reproductive females was small in this study, the pattern detected was expected as the ornament is known to develop and fade in concert with the ovarian cycle (Weiss, 2002), thereby serving as a signal of reproductive state as well as phenotypic quality. Also expected was the increased rate of reproductive suppression among C-IMP females, as it seems selectively advantageous for limited energy resources to be shunted to survival rather than reproduction in the face of an anabolic challenge.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…Though sample size of non-reproductive females was small in this study, the pattern detected was expected as the ornament is known to develop and fade in concert with the ovarian cycle (Weiss, 2002), thereby serving as a signal of reproductive state as well as phenotypic quality. Also expected was the increased rate of reproductive suppression among C-IMP females, as it seems selectively advantageous for limited energy resources to be shunted to survival rather than reproduction in the face of an anabolic challenge.…”
Section: Discussionmentioning
confidence: 78%
“…Reproductive state was also included in our final statistical models as ornament expression is known to vary with reproductive state (Weiss, 2002) and C-IMP females were significantly less likely than other females to produce a clutch of eggs (χ 2 3 =9.04, P=0.03; Table2). Of the females that failed to produce a clutch, ~53% were C-IMP females (N=8), ~20% were autotomized (N=3) and ~13% were in each of the two control groups (N=2 per control group).…”
Section: Reproductive Status and Outputmentioning
confidence: 99%
See 1 more Smart Citation
“…Weiss [199] reptile Uta stansburiana latter viewpoint and West-Eberhard's [12] definition of social selection, wherein sexual selection is a special form of social selection [41]. Placing aspects of fitness within this framework is necessarily somewhat subjective.…”
Section: Review Of Empirical Studiesmentioning
confidence: 99%
“…Most of these studies reported a relationship between female colourations and reproductive state (Ferguson 1976;Cooper et al 1983;Watkins 1997;Cuadrado 2000;LeBas & Marshall 2000;Hager 2001;Weiss 2002;Baird 2004); for example, the throat colouration of female Sceloporus virgatus changes seasonally and the colour intensity peaks near the time of ovulation (Weiss 2002(Weiss , 2006. In some cases, males have been shown to respond to female ornaments by increasing courtship towards ovulating females while reducing courtship to non-receptive females (Baird 2004).…”
Section: Introductionmentioning
confidence: 99%